2015
DOI: 10.1308/003588414x14055925059318
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of reoperations for orthopaedic trauma

Abstract: INTRODUCTION The Royal College of Surgeons of England (RCS) has issued guidance regarding the use of reoperation rates in the revalidation of UK-based orthopaedic surgeons. Currently, little has been published concerning acceptable rates of reoperation following primary surgical management of orthopaedic trauma, particularly with reference to revalidation. METHODS A retrospective review was conducted of patients undergoing clearly defined reoperations following primary surgical management of trauma between 1 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Previous studies have been limited by composite outcome analyses in which mechanical/technical failures were grouped with other complications such as wound dehiscence, infection, medical complications, or hardware removal. 1,14,41,48,54,56 We excluded cases revised alongside wound complications while expanding the study window to 12 months in hopes of analyzing not only early reoperations based on technical failures but also those performed for mechanical failures of fixation or delayed/nonunion. Additionally, we compared our adequately powered revision cohort to a matched control group and analyzed data using both univariate and multivariable analyses to minimize confounders and maximize the clinical applicability of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have been limited by composite outcome analyses in which mechanical/technical failures were grouped with other complications such as wound dehiscence, infection, medical complications, or hardware removal. 1,14,41,48,54,56 We excluded cases revised alongside wound complications while expanding the study window to 12 months in hopes of analyzing not only early reoperations based on technical failures but also those performed for mechanical failures of fixation or delayed/nonunion. Additionally, we compared our adequately powered revision cohort to a matched control group and analyzed data using both univariate and multivariable analyses to minimize confounders and maximize the clinical applicability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…While early reoperation rates (within 12 months of index ORIF) are low, from 0.82% to 3.7% in most series, reports as high as 7.8% have been published. 1,5,26,31,42,48,56,60 Multiple previous studies have investigated the incidence of and risk factors associated with wound complications after operative treatment. 14,33,37,48,62 Similarly, work by Ovaska et al 42 identified technical errors leading to the need for acute revision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a conservative decision based on reoperation data. 16 This also meant that in patients with bilateral fractures, only the first documented fracture was counted.…”
Section: Identification Of Distal Radius Fracturementioning
confidence: 99%
“…Up to 1.9% of patients undergoing an orthopedic trauma procedure have been shown to require an unplanned reoperation, 43 and in the context of the significant costs associated with a hospital bed day, 44 reduced rate of reoperation can be associated with an improvement in economic burden in addition to the obvious patient benefits. In previous studies, the rate of reoperation was lower in the separate device cohort, 25 which is consistent with the findings of this review, in which 11.1% of the nail cohort proceeded on to having at least one further orthopedic intervention, versus 6.25% of the separate device cohort.…”
Section: Discussionmentioning
confidence: 99%